2009
DOI: 10.1136/ard.2008.106567
|View full text |Cite
|
Sign up to set email alerts
|

The TRAF1-C5 region on chromosome 9q33 is associated with multiple autoimmune diseases

Abstract: A significant association was found for the TRAF1-C5 locus in SLE, implying that this region lies in a pathway relevant to multiple autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 27 publications
1
45
1
1
Order By: Relevance
“…Associations between single-nucleotide polymorphisms (SNPs) of TNFSF4 and TRAF1-C5 and SLE have been reported in different ethnic groups [10][11][12][13][14][15][16][17][18][19][20][21][22]. Typically, the allelic frequencies of genes often differ substantially in different ethnic groups, and thus, ethnically specific association studies are required to determine genetic associations in different populations [23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…Associations between single-nucleotide polymorphisms (SNPs) of TNFSF4 and TRAF1-C5 and SLE have been reported in different ethnic groups [10][11][12][13][14][15][16][17][18][19][20][21][22]. Typically, the allelic frequencies of genes often differ substantially in different ethnic groups, and thus, ethnically specific association studies are required to determine genetic associations in different populations [23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…rs6920220 is consistently associated with rheumatoid arthritis (RA) risk [228], and the results for other polymorphisms of the TRAF1 gene in relation to this disease are contradictory. The A allele of the rs10818488 polymorphism may correlate with a higher risk of SLE [229]. However, data regarding the association of TRAF1 gene polymorphisms with diseases other than cancer remain elusive, but it is possible to recommend rs4836834, rs2269059, and rs3761846 (short list) and rs6920220, rs10818488, rs3761847, and rs7021206 (extended list) for further oncogenomic investigations.…”
Section: Tnf Receptor-associated Factor (Traf1-traf6) Gene Polymorphimentioning
confidence: 98%
“…Region 9q33 (TRAF1): this region was first associated to rheumatoid arthritis (Kurreeman et al, 2007). Our group took part in a collaborative study that analyzed this region in several autoimmune diseases and found association with type 1 diabetes, among others (Kurreeman et al, 2010). As an extension of the cited study, we selected and studied new polymorphisms in the TRAF1 gene and analyzed their influence in age at onset of the disease.…”
Section: Genome-wide Associationsmentioning
confidence: 99%